Al-Qur’an dan Pengusaha Muslim: Karakter Ir. Sholah Al Athiyah - Munir, Munir; Mais, Rimi Gusliana; Fachri, Muhammad Ridwan (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
The purpose of this article is to analyze the behavior of a successful entrepreneur named Ir. Sholah Al Athiyah is based on the teachings of the Koran and to fill the void in Muslim entrepreneurship literature and to reveal new findings that have not been explored by other researchers. Ir. Sholah Al Athiyah is an entrepreneur and businessman who lives in Egypt. The exact definition of the term entrepreneurship is still being discussed, so that research on entrepreneurship remains relevant. The source of discussion in this article is the Al-Qur'an, because the study provides a deeper understanding of the basic contents of the Al-Qur'an. Therefore, this article tries to answer the attitude of Ir. Sholah Al Athiyah in Islamic entrepreneurship based on the Koran. This research needs to be carried out considering that the current development of large corporations requires business research that comes directly from the Al-Qur’an as a reference and facts about Islamic figures. This research uses library research methods and examines relevant scientific articles as data sources. The results of this research contain several basic verses about entrepreneurship. This verse relates to the attitude of business actors when running a business. Lastly, the concept of Islamic entrepreneurship would be very suitable to be applied because it contains two meanings Hablumminannas and Hablumminallah, as is the attitude of Ir. Sholah Al Athiyah who always adheres to the values of the verses of the Koran and makes Allah SWT the main investor.